Experimental investigation of biomimetic self-pumping and self-adaptive transpiration cooling. (1st September 2017) - Jiang, Pei-Xue; Huang, Gan; Zhu, Yinhai; Xu, Ruina; Liao, Zhiyuan; Lu, Taojie
Abstract: Transpiration cooling is an effective way to protect high heat flux walls. However, the pumps for the transpiration cooling system make the system more complex and increase the load, which is a huge challenge for practical applications. A biomimetic self-pumping transpiration cooling system was developed inspired by the process of trees transpiration that has no pumps. An experimental investigation showed that the water coolant automatically flowed from the water tank to the hot surface with a height difference of 80 mm without any pumps. A self-adaptive transpiration cooling system was then developed based on this mechanism. The system effectively cooled the hot surface with the surface temperature kept to about 373 K when the heating flame temperature was 1639 K and the heat flux was about 0.42 MW m −2 . The cooling efficiency reached 94.5%. The coolant mass flow rate adaptively increased with increasing flame heat flux from 0.24 MW m −2 to 0.42 MW m −2 while the cooled surface temperature stayed around 373 K. Schlieren pictures showed a protective steam layer on the hot surface which blocked the flame heat flux to the hot surface. The protective steam layer thickness also increased with increasing heat flux.